Preliminary evidence on the neural correlates of timing deficit in post-traumatic stress disorder - Carmelo M. Vicario; Gabriella Martino; Chiara Lucifora; Kim Felmingham (European Journal of Psychotraumatology, 2022)
It has recently been suggested that a deficit in time processing may be considered a cognitive marker of Post-Traumatic Stress Disorder (PTSD). However, the neural correlates of this cognitive deficit in PTSD remain unknown. Voxel-based morphometry and supra-second perceptual time processing data from 8 participants with PTSD and 19 healthy controls have been examined. In line with previous investigations, PTSD patients overestimated the duration of the displayed stimuli. Moreover, their time estimation was more variable than that of controls. Critically, compared to controls, a higher grey matter volume was reported in most of neural regions of PTSD canonically associated with supra-second perceptual timing. These data provide preliminary evidence that the abnormal neuroplasticity of this neural network may be responsible for the altered experience of time in PTSD.